2011
DOI: 10.1080/17408989.2010.532781
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the ideological work of the discourses of ‘fair play’ and moral education in perpetuating inequitable gender practices in PETE

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Dowling, F. J., Kårhus, S. (2011). An analysis of the ideological work of the discourses of 'fair play' and moral education in perpetuating inequitable gender practices in PETE. Physical Education and Sport Pedagogy, 16,[197][198][199][200][201][202][203][204][205][206][207][208][209][210][211].Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…These results coincide with those of Wellard (2011), and it can be stated that teachers generally observe a masculine approach to physical education, leading to girls' lower participation in the classes (Azzarito, 2009;Dowling & Kårhus, 2011;Gard, 2008;Verscheure & Amade-Escot, 2007). The curriculum has certain contents, but the teachers can encourage some preferences that offer possibilities to all the students, and this affects the activities that could be performed out of school.…”
Section: The Curriculum Of Physical Educationsupporting
confidence: 86%
See 1 more Smart Citation
“…These results coincide with those of Wellard (2011), and it can be stated that teachers generally observe a masculine approach to physical education, leading to girls' lower participation in the classes (Azzarito, 2009;Dowling & Kårhus, 2011;Gard, 2008;Verscheure & Amade-Escot, 2007). The curriculum has certain contents, but the teachers can encourage some preferences that offer possibilities to all the students, and this affects the activities that could be performed out of school.…”
Section: The Curriculum Of Physical Educationsupporting
confidence: 86%
“…The theoretical rationale is that boys and girls do not have equal opportunities to participate in the physical activities of physical education classes, and therefore, the benefits are greater for boys than for girls. In other words, teachers direct these activities with a 'masculine' approach (Azzarito, 2009;Dowling & Kårhus, 2011;Verscheure & Amade-Escot, 2007), in the same way that boys understand that certain activities are 'for girls' (Gard, 2008). For example, some sports are considered to be excessively competitive (Dwyer et al, 2006), although it has been shown that differences in competitiveness should not involve sex differences in sport participation (Gill, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Th e gathered data are consistent with Muros Ruitz and Fernández-Balboa's (2005) research results, which showed that the knowledge and understanding of basic defi nitions and principles among the interviewed PE teachers in Spain were in many cases inadequate and inconsistent with the literature. Likewise, while interviewing PE teachers in Norway, Dowling (2008;Dowling, Kårhus, 2011) found that their understanding of gender issues in PE was somewhat lacking, rooted in their biographies and common-sense understanding rather than being theoretically formed. Th e obtained data lead to the conclusion that among the teacher's competences mentioned in the fi rst paragraph, knowledge is the primary one.…”
Section: Discussionmentioning
confidence: 99%
“…Research on reflexive practices prove it is difficult for teachers to focus the complexity of relations and influences from society, including gender ones. Dowling and Kårhus (2011) proved how teachers' discourses are simplified, aligned on generic conceptual values (game rules, transferring team work values) excluding all other influences, including gender ones. School is not the only agency where stereotyped gender roles can survive, however its mission is to criticise, rather than ignore or legitimise these.…”
Section: Methodological Dimension: Mediation Between the Subject Of Lmentioning
confidence: 99%